Pengaruh Ankle Strategy Exercise Terhadap Tingkat Risiko Jatuh Pada Komunitas Lansia Di Kelurahan Jagir RW 1 Kecamatan Wonokromo - Yudistira Dimas Puhwanto; Fransisca Xaveria Hargiani; Amin Zakaria; Yohanes Deo Fau (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Ankle Strategy Exercise is an exercise with controlled movement and is centered on the ankle so that the body postural muscle from distal to proximal will be optimally activated. The risk of falling occurs in the elderly as time goes by with increasing age. Falling is a cause of injury, broken bones and complications related to damage to the body structure which will cause immobilization and fear of falling again so that the elderly are less willing to move. Methods: This research has 15 respondents using probability. The research design uses a pre-experimental type with a one group pretest and posttest approach Results: The result in this study, there was an effect of ankle strategy exercise on risk falls at the elderly community in Jagir RW 1 , Wonokromo District branch with a p-value = 0.000 (p<0.05)Conclusion: There is an influence of the ankle strategy exercise on changes in the results of the timed up and go test for the elderly group in the Jagir RW 1 Village, Wonokromo District with a Paired T-Test significance of 0.000<α (α=0.05).